MODEL PENERAPAN INTEGRATED RESERVATION SYSTEM DENGAN PLATFORM DIGITAL PADA HOTEL MERCURE BALI LEGIAN - Darael, Jane; Lagarense, Bet El Silisna; Andih, Deisy C (PolimdoSains, 2024)
The development of technology is so fast without knowing the team and has become a very basic need for various groups, one of which is hospitality. Various quality information System applications can be realized through a good information System application model. Information Systems can provide benefits and advantages for hoteliers and guests. The implementation of an integrated reservation information System with digital platforms in hotels can improve operational efficiency, improve guest experience, and increase profits for hotels. Especially in the hotel reservation section to obtain data, and process guest data. The presence of an integrated online reservation System makes it convenient to book lodging. The reservation System used by Mercure Bali Legian Hotel is feasible to use because it has been integrated and makes it easier for staff, especially the reservation department to apply and process guest data. Through the Integrated Reservation System, you can increase room bookings from various platforms. This cooperation relationship is mutually beneficial and needs each other, and no one party suffers losses because of this cooperation, because the cooperation relationship with online travel agents is clear and the services provided are in accordance with procedures and agreements that have been agreed and made together. Mercure Bali Legian benefits because guests can easily make a reservation process through an online travel agent, while online travel agents benefit from viewers who have accessed the application